2014
DOI: 10.1139/cjc-2013-0427
|View full text |Cite
|
Sign up to set email alerts
|

Germanium-centered free radicals studied by muon spin spectroscopy

Abstract: Transverse-field muon spin rotation (TF-SR) spectra have been recorded for free radicals formed by positive muon irradiation of nine different divalent germanium compounds. Muon-electron hyperfine coupling constants (A ) were determined from the spectra and compared with values predicted from density functional theory molecular orbital (DFT-MO) calculations on the muoniated radicals formed by muonium addition to the germanium atom. The muon hyperfine constants for germylenes containing N-Ge bonds are generally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 35 publications
0
9
0
1
Order By: Relevance
“…91 The UV/visible spectrum for 114 displays absorption bands at l max = 531 nm and 383 nm, 85 whilst 123 exhibits two absorption bands at l max = 399 nm and 472 nm, 91 which are similar to the pp* and n Àn + transitions for multiply bonded digermynes, indicating a significant electronic difference between these systems. 97 The spectrum is consistent with cyclohexadienyl radicals formed by competitive addition of muonium to the five aromatic rings of the ligand. The greater steric bulk of the [ i Pr 3 Si(Ar † )N] À ligand prevents the planarisation of the Ge 2 NSiC fragments in 123 which disallows N -Ge p-bonding.…”
Section: Group 14 Complexesmentioning
confidence: 60%
“…91 The UV/visible spectrum for 114 displays absorption bands at l max = 531 nm and 383 nm, 85 whilst 123 exhibits two absorption bands at l max = 399 nm and 472 nm, 91 which are similar to the pp* and n Àn + transitions for multiply bonded digermynes, indicating a significant electronic difference between these systems. 97 The spectrum is consistent with cyclohexadienyl radicals formed by competitive addition of muonium to the five aromatic rings of the ligand. The greater steric bulk of the [ i Pr 3 Si(Ar † )N] À ligand prevents the planarisation of the Ge 2 NSiC fragments in 123 which disallows N -Ge p-bonding.…”
Section: Group 14 Complexesmentioning
confidence: 60%
“…The purpose of this conference was to bring together researchers whose interests span the chemistry of germanium, tin, and lead, and this collection of manuscripts reflects the diverse range of topics presented at the conference: from the synthesis of low coordinate molecules as illustrated in the work presented by Jones 1 and studies of the reactivity of these interesting species as reported by Růžička, 2 Tokitoh 3 Willem, 4 and Baines 5 to the synthesis of high coordinate supramolecular structures as demonstrated in the work of Reuter; 6,7,8 from muon spin spectroscopy of germanium radicals as studied by West 9 to nuclear magnetic resonance spectroscopy 4 of Sn(II) and Sn(0) complexes; from the synthesis of ternary metal clusters as reported by Molloy 10 to polymers and their model oligomers as synthesized by Foucher 11 and Weinert, 12 respectively. Saito, 13 Shankar, 14 and Uhlig 15,16 describe their research on the high yielding synthesis and extended structures of several important functional tin(IV) compounds.…”
mentioning
confidence: 85%
“…These species serve as models for the NH divalent species, with usually large substituents attached to the nitrogen atoms, that have been considered by the muon spin resonance spectroscopy techniques in recent years. 19,20,[128][129][130][131][132][133][134][135][136] Most of these divalent species were once considered as unstable and inaccessible but were eventually synthesized and found vast applications in various fields of chemistry. Some classic reviews on the original studies are Ref.…”
Section: B Applicationsmentioning
confidence: 99%
“…[137][138][139][140][141] At the next step, a hydrogen atom was added to each parent structure in order to model the attachment of the muonium atom to these molecules, as is common in the relevant literature. [129][130][131][132][133][134][135][136] In principle, the hydrogen atom may be attached to the divalent center or to one of the "unsaturated" carbons with a double bond in between resulting in two distinct adducts. Each adduct is named by the following convention: the attached hydrogen atom to the parent molecule is given first followed by the name of the atom to which it is attached, and finally, the parent molecule name itself is indicated, e.g.…”
Section: B Applicationsmentioning
confidence: 99%